2010
DOI: 10.1007/s10562-010-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Ce/N-Codoped TiO2 Particles for Production of H2 by Photocatalytic Splitting Water Under Visible Light

Abstract: Cerium and nitrogen codoped TiO 2 photocatalysts were successfully prepared by sol-gel method. The results showed that Ce doped in TiO 2 could prevent phase transition of anatase to rutile and inhibit the growth of crystallite. In addition, Ce and N codoped in TiO 2 enhanced the lattice distortion. N-Ti bond and N-Ti-O bond were formed in codoped titania, which narrowed the energy gap and extended the absorption edge to the visible light range, and the synergistic effects of the Ce and N codoped samples made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 32 publications
3
62
1
Order By: Relevance
“…In this case, the substitution of cerium ions (Ce 3+ and Ce 4+ ) in the TiO 2 framework, as suggested by DRS measurements, was the key factor for having a good performance. The cerium defects act, in fact, as hole traps [39,40,63], avoiding the recombination of active electrons and holes and thus favoring the reduction of water. In this case, gold positively affects the photocatalytic performance, both increasing the defective structure of ceria, as shown by Raman, and favoring the enrichment of ceria on the surface of TiO 2 , as shown by EDX, thus explaining the highest H 2 production rate of the Au/TiO 2 -10%CeO 2 system.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the substitution of cerium ions (Ce 3+ and Ce 4+ ) in the TiO 2 framework, as suggested by DRS measurements, was the key factor for having a good performance. The cerium defects act, in fact, as hole traps [39,40,63], avoiding the recombination of active electrons and holes and thus favoring the reduction of water. In this case, gold positively affects the photocatalytic performance, both increasing the defective structure of ceria, as shown by Raman, and favoring the enrichment of ceria on the surface of TiO 2 , as shown by EDX, thus explaining the highest H 2 production rate of the Au/TiO 2 -10%CeO 2 system.…”
Section: Discussionmentioning
confidence: 99%
“…XPS analysis is of useful application to the much studied class of Ce-bearing catalysts [2][3][4][5], because it provides straightforward access to the chemistry of the cerium, and this is also a central issue in both the scope and aims of Sun et al's paper [1]. My comment will focus on the authors' interpretation of the XPS Ce3d spectra of sample Ce(1.2%)-N-TiO 2 analyzed as-inserted (Fig.…”
mentioning
confidence: 99%
“…In a recent paper, Sun et al reported on the preparation and characterization of cerium-nitrogen-doped TiO 2 photocatalysts, and used X-ray photoelectron spectroscopy (XPS) to map the oxidation state of the chemical elements present therein [1]. XPS analysis is of useful application to the much studied class of Ce-bearing catalysts [2][3][4][5], because it provides straightforward access to the chemistry of the cerium, and this is also a central issue in both the scope and aims of Sun et al's paper [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations